Growth and Yield of Cowpea Microgreens (Vigna unguiculata L. Walp) under Different LED Light Intensities and Growing Media - Wiliem, Steven De; Zumani, Darul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Cowpea microgreens (Vigna unguiculata L. Walp) are nutrient-rich foods with high nutritional content. The objective of this research was to ascertain how growing medium and 6500K white LED light intensity affected the development and production of cowpea microgreens. This investigation was conducted in January and February of 2025 in Nagarawangi Village, Cihideung Subdistrict, Tasikmalaya City, at a height of 355 meters above sea level. Using a factorial randomised block design, the research used an experimental approach with two components: two kinds of growth medium (m1 (rockwool) and m2 (vermicompost)) and five degrees of light intensity (i0 (control), i1 (3000 lux), i2 (4000 lux), i3 (5000 lux), and i4 (6000 lux). Every therapy was carried out three times. The observational data were analyzed at a significance level of 5% using the Analysis of Variance (ANOVA) and Duncan's Multiple Range Test (DMRT). The findings indicated that fresh weight and germination speed parameters were influenced by both growth material and light intensity. Microgreens' height and germination rate were influenced by light intensity and growth medium separately. Based on the results, the treatment of 5000 lux light intensity with rockwool growing media produced the best growth and yield of cowpea microgreens (Vigna unguiculata L. Walp).